The Role of MSMEs in Economic Policy in Banten Province - Hadiaty , Siti; Surya, Dhika (International Journal of Humanities, Law, and Politics, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play an important role in supporting the economy in Banten Province, with significant contributions to GRDP, job creation, and key sectors such as trade, manufacturing, and tourism. However, despite their great economic potential, MSMEs in Banten still face complex challenges, such as difficulties in accessing capital, low financial literacy, and dependence on local political policies. This study aims to analyze the role of MSMEs in political economic policies in Banten Province, identify the challenges faced by MSME actors, and provide policy recommendations that can improve the competitiveness of MSMEs in the region. The method used in this study is a qualitative approach with a case study method, which focuses on several cities and districts in Banten, such as Tangerang City, Serang City, and Pandeglang Regency. Data collection was carried out through in-depth interviews with MSME actors, local government officials, and related organizations, as well as direct observation at MSME business locations. The data obtained were then analyzed using a thematic analysis approach. The results of the study show that although government programs to support MSMEs have been launched, their distribution is not evenly distributed, especially in remote areas. The main challenges faced are limited access to capital, dependence on political decisions, and low financial literacy. In addition, digitalization is a great opportunity, but limited infrastructure is an obstacle. Based on these findings, the study provides policy recommendations, such as increasing access to financing, financial literacy training, equalizing assistance programs, and strengthening digital infrastructure to support the sustainability and growth of MSMEs in Banten.